Intranasal immunization with inactivated tick-borne encephalitis virus and the antigenic peptide 89–119 protects mice against intraperitoneal challenge - Goncharova, Elena; Ryzhikov, Evgeny; Poryvaev, Vasily; Bulychev, Leonid; Karpyshev, Nikolay; Maksyutov, Amir; Ryzhikov, Alexander B. (International journal of medical microbiology, 2006)
Detailed studies of the pathogenesis of certain neuroviral infections allow for a better understanding of the special role of the olfactory neuroepithelial cells in the invasion of viruses into the CNS. Several studies using animal models demonstrated that neurotropic viruses belonging to various families invade the brain via the olfactory tract after parenteral infection. We suppose that intranasal (i.n.) immunization inducing mucosal and systemic immunity will block neurotropic virus propagation into the brain via the olfactory pathway and neutralize virus multiplication in visceral organs. Subject of the present study was the efficacy of i.n. immunization of Balb/c mice with both killed tick-borne encephalitis (TBE) virus and antigenic peptide 89–119 from the envelope protein E of TBE virus in a nanoemulsion formulation. Intranasal immunization with nanoemulsion containing inactivated TBE virus particles induced specific both neutralizing and HAI antibodies. TBE virus specific IgA antibodies were detected in lung and nasal lavages of mice. The fourth i.n. immunization resulted in a drastic titer increase of the specific antibodies to 1:12,800, which was protective in all i.n. immunized mice against intraperitoneal (i.p.) challenge with 100 LD 50 of TBE virus. The ratio of specific IgG2a to IgG1 indicated the occurrence of a Th2 type immune response. We observed a similar balance of TBE virus-specific IgG2a/IgG1 after s.c. immunization of mice with the commercial FSME-Immun Inject ® vaccine against TBE virus. Thus, the experimental data obtained for the first time demonstrates the feasibility of using nanoparticles containing inactivated TBE virus for effective protection of i.n. immunized mice against the usually lethal infection. We analyzed a number of fragments of E protein of the TBE virus for antigenic similarity with human proteins by computer analysis. Local antigenic similarity of the fragments of E protein of TBE virus and human proteins allows for the identification of the epitopes, which may induce an autoimmune response if applied in a vaccine construct. One of the candidates, peptide 89–119 of E protein of the TBE virus does not contain any epitopes with local similarities to human protein epitopes. This peptide was synthesized and applied intranasally in nanoparticulate formulation. It induced TBE virus-specific antibodies and led to protection in the case of i.p. challenge with TBE virus.